Modernizing Copyright with the Least Directive on Copyright in the Digital Single Market 2019/790 - Atanasova, Hristina (Research Papers, 2020)
The article contains an analysis of the new regulation of copyright in the digital single market according to the adopted Directive (EU) 2019/790 of the European Parliament and of the Council of 17 April 2019 on copyright and related rights in the digital single market and amending directives 96 / 9 / EC and 2001/29 / EC2019 / 790. It is one of the measures the EU is taking to modernize the existing regulatory framework. The study covers the reasons for the adoption of the directive, its nature and the expected results.